LEGAL PROTECTION FOR MSMEs IN ONLINE TRANSACTIONS - Iqbal Naufal; Nur Amanda Dalimunthe; Oktatia Ramadhani Afhar; Rizky Ananda (LEX SOCIETAS: Journal of Law and Public Administration, 2025)
The rapid advancement of digital technology has encouraged Micro, Small and Medium Enterprises (MSMEs) to shift to online-based commerce. This transformation offers greater market access and operational convenience, but also brings legal risks such as online fraud, contract disputes, and misuse of personal data. This research aims to examine the legal protections available to MSMEs in online transactions under Indonesian law and to identify the challenges faced in its implementation. This research uses a normative juridical method by analyzing relevant laws and legal literature. The findings show that legal protection for MSMEs is regulated in several legal frameworks, including the Electronic Information and Transaction Law (ITE Law), Consumer Protection Law, and regulations regarding MSMEs. However, its implementation is still hampered by several issues such as low legal literacy among MSME actors, limited access to legal aid, and weak supervision of digital platforms. Therefore, it is important to improve legal education, develop a more responsive legal framework, and encourage collaboration among stakeholders to build a safe and fair digital transaction ecosystem for MSMEs